PUPPET THERAPY AS A PEDAGOGICAL TOOL FOR SOLVING PROBLEMS OF CHILD SOCIALIZATION (EDUCATION IN THE 21ST CENTURY, 2023)
Puppet therapy is one of the most widely used art technologies in arttherapy today, which reveals the phenomenon of puppets in a new sense in art pedagogy as a newpedagogical “tool” from the aspect of role behavior development, relieving emotional tension,preventing or correcting behavioral disorders. Its different types are distinguished not only by theway they are performed, but also by the direction of the work with the child: corrective,informative, regulatory, etc. Puppet therapy is often intertwined with imagotherapy and dramatherapy, where one of the most important issues in the development of a person's personality- thestudy of his image, becomes a priority. Puppet therapy is intended for children of all ages, but forchildren of different ages, its role, significance and impact, the functions performed are different.This interesting art technology is implemented individually and in groups. Puppet therapy has amultifaceted effect on the regulation of child behavior and emotional disorders.
Keywords: Puppet therapy, imagotherapy social status, social role, emotional disorders, role behavior, social behavior, puppet theater, puppet show, required, subjective, feature roles, inclusive theater.